PENGARUH KONSENTRASI NATRIUM CARBOXYMETHYL CELLULOSE DAN ASAM SITRAT TERHADAP KUALITAS SARI BUAH MELON - Suparno Suparno; Tinting Ruben (AgriPeat, 2016)
This research aims to improve the effect concentration of citric acid and Na CMC as a preservative appropriate on the quality of chemical and organoleptic characteristic of melon juice. The factorial completely randomized block design with four replications was applied on this research. First factor was concentration of citric acid (0,1; 0,2; dan 0,3 % b.v-1). Second factor is concentration Na CMC (0,25; 0,35; dan 0,45 % b.v-1). The results showed that the interaction betwen citric acid and Na CMC concentration was not significantly effect to total acid, reduction of glucose, ascorbat acid, and the elarity of organoleptic test and taste, while the separate of water percentage significant effect between treatments. The best treatment for producing of melon juice was citric acid and Na CMC with a concentration of 0, 2 % b.v-1 and 0,45 % b.v-1. It is recommended also for further research conducted on the effects of temperature and pH on the stability of Na CMC as a stabilizer of fruit puree or juice drinks melon